ANALYSIS OF TEACHING AND LEARNING ACTIVITIES TO DETERMINE THE QUALITY OF STUDENT LEARNING USING THE K-MEANS CLUSTERING METHOD(CASE STUDY OF SMK MAARIF AL-MIZAN) - Muhammad Abdul Jabbar; Fikri Emsa Silmi; Ahmad Teguh Satria (Journal of Multimedia Technology and Applied Software, 2024)
In the world of education there are often problems how to determine the quality in an educational institution and often institutions ignore it, therefore to find out the quality of education in an institution requires clustering using the K-Means method which will be divided into 3 (three) cluster levels, namely "A" for very good quality levels, "B" for good quality levels and "C" for low education quality levels and to determine the quality of institutions We used data on the average report card of grade X, XI, XII students of all majors for one year.